2017
DOI: 10.12968/bjcn.2017.22.sup9.s30
|View full text |Cite
|
Sign up to set email alerts
|

Chronic leg ulcers disrupt patients' lives: A study of leg ulcer-related life changes and quality of life

Abstract: Chronic leg ulcers have a profound impact on patients' physical, functional, and psychological status, which may result in several life changes and a significant decline in quality of life (QoL). We aimed to study what changed in patients' lives after developing a chronic leg ulcer, including QoL, patients' comprehension of the disease and related feelings. A cross-sectional study, using an anonymous questionnaire and the Dermatology Life Quality Index (DLQI) was performed. Chronic leg ulcers were life changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Unlike previous studies of factors associated with ulcer‐related pain, we found no significant association between several biological factors (i.e., wound diagnosis, ulcer size, ulcer duration) and moderate to severe ulcer‐related background pain. Even though there are differences in the pathologies and clinical characteristics of different types of chronic leg ulcers, all chronic leg ulcers are associated with a profound impact on persons’ physical, functional and psychological status (Cunha et al, 2017; Franks & Morgan, 2003; Herber et al, 2007). Pain is a biopsychosocial phenomenon (IASP, 2020), and it is acknowledged that the size and severity of an injury is not always related to the pain experienced (Chapman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies of factors associated with ulcer‐related pain, we found no significant association between several biological factors (i.e., wound diagnosis, ulcer size, ulcer duration) and moderate to severe ulcer‐related background pain. Even though there are differences in the pathologies and clinical characteristics of different types of chronic leg ulcers, all chronic leg ulcers are associated with a profound impact on persons’ physical, functional and psychological status (Cunha et al, 2017; Franks & Morgan, 2003; Herber et al, 2007). Pain is a biopsychosocial phenomenon (IASP, 2020), and it is acknowledged that the size and severity of an injury is not always related to the pain experienced (Chapman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since the incidence of wounds rise with age, the prevalence is likely to rise as the population ages (Atkin et al, 2019). All types of chronic leg ulcers, irrespective of pathology, are associated with a negative impact on patients’ physical and psychosocial function and health status which may result in a significant decline in quality of life (Cunha et al, 2017; Franks & Morgan, 2003; Herber et al, 2007). In addition, chronic wounds are a major financial burden to the society (Olsson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These variables are among the worst characteristics associated with the chronic wound, and they can cause embarrassment and lead patients to exclude themselves from society in an attempt to avoid moments of repression, generating feelings of solitude and depression. (20) Wound exudate is an excess of leaky fluid that usually builds up in the injured tissue. Exudation is a serious problem due to the presence of proteases that destroy the tissue and directly contribute to the increase of the wound size.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the present study, more than half of the participants had other painful comorbidities such as musculoskeletal pain, joint pain, and neuropathies. Previous research also shows that the ulcer itself, 63 older age, 64 and comorbidities 65 are associated with impaired function and health outcomes. Recognising that ulcer related pain in addition to other factors can interfere with several aspects of a person's life are reasons to use biopsychosocial approaches in wound management.…”
Section: Discussionmentioning
confidence: 99%